KEBIJAKAN LAYANAN SYARIAH (OFFICE CHANNELLING) DALAM MENINGKATKAN PANGSA PASAR PERBANKAN SYARIAH - Suryani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This article describes regulations of Bank Indonesia (No. 8/3/PBI/2006) concerning about the conversion of business of conventional commercial banks to commercial banks conducting business based on sharia principle and establishment of bank offices conducting business based on sharia principle by conventional commercial banks (Office Channeling). This regulation is also intended to improve public access to the services of Islamic banking with a new system that Islamic banks do not need to open branch Sharia (UUS) in many places in providing Islamic banking services, so that the cost of the expansion is much more efficient. Office Channeling is also expected to direct the activities of banks to be able to support the growth of the national economy through the activities of Islamic banking. Implementation of this regulation will enable society to Islamic transactions.